Pooled analysis of stereotactic ablative radiotherapy for primary renal cell carcinoma: A report from the International Radiosurgery Oncology Consortium for Kidney (IROCK). Issue 5 (20th December 2017) - Siva, Shankar; Louie, Alexander V.; Warner, Andrew; Muacevic, Alexander; Gandhidasan, Senthilkumar; Ponsky, Lee; Ellis, Rodney; Kaplan, Irving; Mahadevan, Anand; Chu, William; Swaminath, Anand; Onishi, Hiroshi; et al.
Abstract : BACKGROUND: Stereotactic ablative radiotherapy (SABR) is an emerging therapy for primary renal cell carcinoma. The authors assessed safety, efficacy, and survival in a multi‐institutional setting. Outcomes between single‐fraction and multifraction SABR were compared. METHODS: Individual patient data sets from 9 International Radiosurgery Oncology Consortium for Kidney institutions across Germany, Australia, the United States, Canada, and Japan were pooled. Toxicities were recorded using Common Terminology Criteria for Adverse Events, version 4.0. Patient, tumor, and treatment characteristics were stratified according to the number of radiotherapy fractions (single vs multiple). Survival outcomes were examined using Kaplan‐Meier estimates and Cox proportional‐hazards regression. RESULTS: Of 223 patients, 118 received single‐fraction SABR, and 105 received multifraction SABR. The mean patient age was 72 years, and 69.5% of patients were men. There were 83 patients with grade 1 and 2 toxicity (35.6%) and 3 with grade 3 and 4 toxicities (1.3%). The rates of local control, cancer‐specific survival, and progression‐free survival were 97.8%, 95.7%, and 77.4%, respectively, at 2 years; and they were 97.8%, 91.9%, and 65.4%, respectively, at 4 years. On multivariable analysis, tumors with a larger maximum dimension and the receipt of multifraction SABR were associated with poorer progression‐free survival (hazard ratio, 1.16 [ P  < .01] and 1.13 [ P  = .02], respectively) and poorer cancer‐specific survival (hazard ratio, 1.28 [ P  < .01] and 1.33 [ P  = .01], respectively). There were no differences in local failure between the single‐fraction cohort (n = 1) and the multifraction cohort (n = 2; P  = .60). The mean ( ± standard deviation) estimated glomerular filtration rate at baseline was 59.9 ± 21.9 mL per minute, and it decreased by 5.5 ± 13.3 mL per minute ( P  < .01). CONCLUSIONS: SABR is well tolerated and locally effective for treating patients who have primary renal cell carcinoma and has an acceptable impact on renal function. An interesting observation is that patients who receive single‐fraction SABR appear to be less likely to progress distantly or to die of cancer. Cancer 2018;124:934‐42. © 2017 American Cancer Society . Abstract : Stereotactic ablative radiotherapy is well tolerated and effective for primary renal cell carcinoma with an acceptable impact on renal function. Patients who receive single‐fraction stereotactic ablative radiotherapy appear to be less likely to progress distantly or to die of cancer.